Thomas Kuhn, Paradigm revolution possibilities, and Frausein: Patriarchy seen yet unseen - Bunkum, Susan Maree (Curtin University, 2016)
Engaging the power inherent in ethnography and autoethnography, this thesis explores patriarchy as a phenomenon that has shaped the lives and experiences of women in the past, and in the present. In particular, it examines the impact of patriarchy on education as that institution which facilitates social and cultural reproduction. It wields a challenge to contemporary men and women to enter dialogue towards reaching the full and equal humanity of all.